Cardiac Development: Tracing the history of a heart - Spurlock, Brian; Qian, Li (eLife, 2023)
Newly developed tools will help researchers understand how the human heart develops and build better models to study and treat congenital heart disease.
Keywords: cardiac development; pluripotent stem cells; cardiomyocyte; lineage tracing; genetic engineering; transcription factors